Supplementation of mineral compounds in sago hampas hydrolysate for bioethanol production by saccharomyces cerevisiae - Ullifah, Binti Masykuri (Universiti Malaysia Sarawak (UNIMAS), 2013)
Bioethanol is one of the technologies developed by scientist with a possibility of replacing nonrenewable sources of energy. The bioavailability of metal ions in fermentation media are indeed important factors that influence yeast cell physiology and production of yeast fermentation products (Walker et al., 2006).In this study, starchy lignocellulosic from agricultural waste which is sago hampas hydrolysate (SHH) was used as substrate (carbon sources) for ethanol fermentation by baker's yeast (Saccharomyces cerevisiae). The effect of mineral compounds on the rate of fennentation and consequently the production of bioethanol was determined in order to reduce unnecessary cost payout; which is important in large scale bioethanol production. Three types of mineral compounds; magnesium, calcium and zinc were studied. The most suitable metal ionic compound for supplementation of ethanol production from SHH was 0.4 giL calcium and 0.8 giL magnesium. The production of bioethanol from SHH was carried out through batch fermentation process by Saccharomyces cerevisiae at initial pH 5.5 to 5.6, temperature of 30·C in 100 mL working volume.